Applied .NET attributes - Barnaby, Tom.; Bock, Jason (New York : Apress, 2003)
This book focuses on a part of .NET called "attributes". Attributed programming is a feature of .NET that is still relatively unexplored and unknown, yet is extremely important and will become more important over time. Attributes are used to modify the runtime behavior of code in the .NET framework. The book covers the fundamentals of attributes, common .NET attributes, use of custom attributes, and advanced techniques.
Attributes are used to modify the runtime behavior of code in the .NET Framework. Applied .NET Attributes explores the application of .NET attributes and how developers can write custom attributes that provide the maximum level of code reuse and flexibility. Attributed programming is a feature of .NET that is still relatively unexplored and unknown. Because attributes are used to modify the runtime behavior of code in the .NET Framework, their use is extremely important and will become even more important over time. This insightful guide covers the fundamentals of attributes, common .NET attributes, the use of custom attributes, and advanced techniques. Table of Contents Attribute Fundamentals Compile-time and Design-time Attributes Attributes and Runtime Behavior Building Custom Attributes Applying Custom Attributes
Attribute Fundamentals -- nbsp -- Attributes and Compilers -- nbsp -- Attributes and Run-Time Behavior -- Custom Attributes -- nbsp -- Application of Custom Attributes.
Includes index.
1
Keywords: CIT; Application software -- Development